LAYANAN E-BUSINESS PADA JASA SERVICE ELEKTRONIK BERBASIS ANDROID - Risma Petrus; Makarius Bajari (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The need for an online-based service system arises because of the competition that arises in the service business regarding the price that is a consideration in using service; The level of community mobility is very high, it becomes one of the problems in dealing with various electronic damage to household appliances and repairs to house building are found to be very difficult to handle quickly, it takes days to complate so that it becomes an obstacle if the use of service is not observant in choose a service.